Fully Convolutional Color Constancy with Confidence-weighted Pooling - Hu, Yuanming; Wang, Baoyuan; Lin, Steve (2012)
Improvements in color constancy have arisen from the use of convolutional neural networks (CNNs). However, the patch-based CNNs that exist for this problem are faced with the issue of estimation ambiguity, where a patch may contain insufficient information to establish a unique or even a limited possible range of illumination colors. Image patches with estimation ambiguity not only appear with great frequency in photographs, but also significantly degrade the quality of network training and inference.